BALANCED SCORECARD IMPLEMENTATION AND BUDGET PERFORMANCE: THE MODERATING ROLE OF ORGANIZATIONAL CULTURE - Anastasia Yuanita Florenthe Lacaden; Selfiani Selfiani (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2025)
This study aims to examine the effect of the implementation of the Balanced Scorecard on budget performance, with organizational culture as a moderating variable within the Secretariat General of the House of Representatives of the Republic of Indonesia (Setjen DPR RI). The research is grounded in the importance of performance measurement that not only focuses on financial aspects but also incorporates non-financial dimensions that support the achievement of performance-oriented outcomes. The Balanced Scorecard is employed as a strategic measurement tool to assess the effectiveness of budget implementation through its four key perspectives: financial, customer, internal business processes, and learning and growth. A quantitative research method was used, with data collected through questionnaires distributed to 80 respondents consisting of employees across three main divisions: the Finance Administration Division, the State Asset Administration Division, and the Travel Management Division. Data analysis included validity testing, reliability testing, and classical assumption testing to ensure the feasibility of the research model. The findings reveal that the Balanced Scorecard has a positive effect on budget performance, and that organizational culture significantly moderates the relationship between the Balanced Scorecard and budget performance. Thus, this study strengthens the argument that synergy between a structured performance measurement system and a strong organizational culture is essential to achieving accountability and efficiency in public sector budget management.